2008
DOI: 10.1038/nature07273
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for recognition of hemi-methylated DNA by the SRA domain of human UHRF1

Abstract: Epigenetic inheritance in mammals is characterized by high-fidelity replication of CpG methylation patterns during development. UHRF1 (also known as ICBP90 in humans and Np95 in mouse) is an E3 ligase important for the maintenance of global and local DNA methylation in vivo. The preferential affinity of UHRF1 for hemi-methylated DNA over symmetrically methylated DNA by means of its SET and RING-associated (SRA) domain and its association with the maintenance DNA methyltransferase 1 (DNMT1) suggests a role in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
411
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 423 publications
(433 citation statements)
references
References 22 publications
17
411
3
2
Order By: Relevance
“…19,21,23,24 UHRF1 (also known as ICBP90) has recently been shown to play an important role in methylation maintenance. 25 It has the ability to bind hemimethylated DNA through its SET-and RING-associated domain, 26,27 triggering the recruitment of DNMT1 25,28 and histone deacetylace-1. 29 UHRF1-knockout mouse embryonic stem cells exhibit significant loss of genomic methylation.…”
mentioning
confidence: 99%
“…19,21,23,24 UHRF1 (also known as ICBP90) has recently been shown to play an important role in methylation maintenance. 25 It has the ability to bind hemimethylated DNA through its SET-and RING-associated domain, 26,27 triggering the recruitment of DNMT1 25,28 and histone deacetylace-1. 29 UHRF1-knockout mouse embryonic stem cells exhibit significant loss of genomic methylation.…”
mentioning
confidence: 99%
“…Recently, it was revealed that UHRF1 plays a central role in transferring DNA methylation status from mother cells to daughter cells. Its SET and RING finger-associated (SRA) domain recognises hemimethylated DNA that appears in newly synthesised daughter DNA strands during duplication of DNA strands through the S phase (Arita et al, 2008;Avvakumov et al, 2008;Hashimoto et al, 2008). The UHRF1 recruits DNA methyltransferase 1 (DNMT1) to the site with proliferating cell nuclear antigen (PCNA) and methylates the newly synthesised strands (Sharif et al, 2007;Achour et al, 2008).…”
mentioning
confidence: 99%
“…La technologie mise en oeuvre devrait également permettre d'envisager le développement de tests de criblage pour identifier des inhibiteurs du basculement de la cytosine méthylée. ‡ The first stage of transmission of an epigenetic character followed by fluorescence aux changements structuraux mineurs accompagnant le basculement des bases [10]. Cette forte augmentation ne se produit que pour les séquences hémi-méthylées et non pour les séquences non méthylées correspondantes.…”
Section: Dnmt1unclassified
“…Cette forte augmentation ne se produit que pour les séquences hémi-méthylées et non pour les séquences non méthylées correspondantes. En outre, cette forte augmentation de fluorescence est abolie quand le domaine SRA est remplacé par une protéine mutante incapable d'induire un basculement de base [10]. Par ailleurs, nous avons véri-fié que (1) les analogues thG et 3HCnt n'affectent pas ou peu la stabilité du double brin d'ADN dans lequel ils sont insérés, et (2) qu'aux positions où ces sondes sont sensibles au basculement de base induit par SRA, ce domaine conserve une affinité préférentielle pour les séquences hémi-méthylées par rapport aux séquences non méthylées.…”
Section: Dnmt1unclassified